Pengaruh Lingkungan Kerja dan Stres Kerja Tehadap Kepuasan Kerja Karyawan di Pabrik Gula Meritjan Kediri - Achmad Rosidi Ansori (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2020)
This study aims to determine the influence of the work environment and work stress on employee job satisfaction at the Meritjan Kediri Sugar Factory. In this study using quantitative data analysis techniques and using observation data collection techniques and using primary data obtained from questionnaires. The sample in this study was 95 employees. The sample is taken by using the Random Sampling technique, which is taking the sample members from the population randomly without paying attention to the strata in the population. Data analysis techniques using Multiple Linear Regression. The results showed that: (1) The work of environment partially influences employee job satisfaction at the Meritjan Kediri Sugar Factory. (2) Job stress partially influences the job satisfaction of employees at Meritjan Kediri Sugar Factory. (3) Work environment and work stress simultaneously affect the job satisfaction of employees at Meritjan Kediri Sugar Factory.